Business Intelligence Transformation through Agile Methodology: Impact on Decision Velocity and Organizational KPIs - Omoize Fatimetu Dako; Temilola Aderonke Onalaja; Priscilla Samuel Nwachukwu; Folake Ajoke Bankole; Tewogbade Lateefat (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
In an era defined by rapid market shifts and growing data complexity, traditional Business Intelligence (BI) frameworks often fall short in delivering timely, actionable insights. This explores the transformative potential of Agile methodology in modernizing BI practices, particularly in enhancing decision velocity and aligning organizational performance with strategic goals. Agile principles—such as iterative development, stakeholder collaboration, and continuous feedback—are increasingly being adopted by data teams to improve the responsiveness, scalability, and impact of analytics initiatives. This examines the theoretical foundations of Agile as applied to the BI lifecycle, detailing how sprint-based development, backlog management, and frequent stakeholder reviews can overcome the rigidity of conventional BI systems. This outlines an Agile BI workflow that accelerates insight delivery while preserving governance and data quality. Furthermore, it analyzes the organizational benefits of this transformation, including reduced time-to-insight, enhanced user satisfaction, and improved alignment between analytical outputs and key performance indicators (KPIs). Empirical examples and case studies from diverse sectors demonstrate measurable gains, such as faster report iteration cycles, better cross-functional collaboration, and tangible improvements in KPIs like customer acquisition, retention, and operational efficiency. Additionally, we address common implementation challenges—ranging from cultural resistance to tooling constraints—and propose mitigation strategies including DataOps, CI/CD pipelines, and Agile-aligned data governance frameworks. The findings suggest that Agile BI not only boosts the speed and relevance of decision-making but also fosters a data-driven culture where experimentation and continuous improvement are normalized. This concludes by recommending that organizations invest in Agile transformation roadmaps, supported by change management and upskilling, to unlock the full potential of BI in an increasingly digital and data-centric world.